2003
DOI: 10.1073/pnas.1633548100
|View full text |Cite
|
Sign up to set email alerts
|

An interacting network of T-box genes directs gene expression and fate in the zebrafish mesoderm

Abstract: T-box genes encode transcription factors that play critical roles in generating the vertebrate body plan. In many developmental fields, multiple T-box genes are expressed in overlapping domains, establishing broad regions in which different combinations of T-box genes are coexpressed. Here we demonstrate that three T-box genes expressed in the zebrafish mesoderm, no tail, spadetail, and tbx6, operate as a network of interacting genes to regulate region-specific gene expression and developmental fate. Loss-of-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
84
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 55 publications
10
84
1
Order By: Relevance
“…1B). At least 11 of these genes have been previously reported to be downregulated in ntl mutant embryos (8,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) and we highlight below several other genes whose expression is genetically regulated by Ntl.…”
Section: Ntl Binds Mesodermally Expressed Genes Involved In Transcripmentioning
confidence: 86%
See 1 more Smart Citation
“…1B). At least 11 of these genes have been previously reported to be downregulated in ntl mutant embryos (8,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) and we highlight below several other genes whose expression is genetically regulated by Ntl.…”
Section: Ntl Binds Mesodermally Expressed Genes Involved In Transcripmentioning
confidence: 86%
“…S1 C and CЈ; Table S6). msgn1 and myod expression fail to initiate in ntl mutant embryos, although expression levels recover during gastrulation or somi- togenesis, respectively (15,21). Regulation of these myogenic factors provides a mechanism by which Ntl can influence muscle cell fate in the posterior of the embryo in addition to a general posterior identity.…”
Section: Ntl Binds Mesodermally Expressed Genes Involved In Transcripmentioning
confidence: 99%
“…This finding raises an important question, namely, what prevents no tail from inappropriately specifying axial mesoderm fate in these cells? A recent study has shown that expression of Tbx6, or even the Tbx6 DNA-binding domain alone, in regions of no tail expression produces similar phenotypes to those resulting from the expression of the No Tail antagonist NtlEnR-myc (Goering et al, 2003). Furthermore, the activity of a Tbx6-myc fusion mimicked that of the NtlEnR-myc construct, antagonizing No Tail activity when coexpressed in animal cap assays.…”
Section: A Conserved Genetic Pathway For Paraxial Mesoderm Vs Notochmentioning
confidence: 99%
“…However, this finding is due to a degree of redundancy early in development that is revealed by analysis of ntl Ϫ ;spt Ϫ double mutants. Although embryos heterozygous for no tail loss-of-function mutations show no phenotypic defects, when combined with loss of spadetail function, an enhancement of the spadetail mutant phenotype occurs (Amacher et al, 2002;Goering et al, 2003). As gastrulation proceeds, the cells of the hypoblast begin to refine their expression of both genes, with spadetail becoming restricted primarily to the paraxial mesoderm progenitors and no tail restricted to the notochord (Schulte-Merker et al, 1992;Griffin et al, 1998).…”
Section: T-box Genes Regulate Paraxial Mesoderm Developmentmentioning
confidence: 99%
“…Mutations in Tbx1 and TBX22 cause craniofacial defects that include cleft palate in mice and humans, respectively (34,35). A recent study in zebrafish (44) showed that closely related T-box transcription factors can interact either synergistically or antagonistically to regulate region specific developmental fate in overlapping expression domains. Further investigation of Tbx10 function in Dc mutants will lead to a better understanding of the molecular pathways involved in craniofacial development and CL͞P pathogenesis.…”
Section: Ectopic Expression Of Tbx10 In Transgenic Mice Recapitulatesmentioning
confidence: 99%